PENGARUH DENTAL BRAILLE EDUCATION (DBE) TERHADAP ORAL HYGIENE PADA ANAK TUNANETRA - Muhammad Fiqih Sabilillah; Rieza Zulfahmi Taftazani; Yayah Sopianah; Dyah Fatmasari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe influence of dental braille education (DBE) to oral hygiene of blind childrenABSTRACTBlind children has poor oral hygiene. Such condition due to tooth brushing is not monitored, other factors such as brushing technique, motor skills and mentoring assistance are still negligible. Besides the lack of visualization to understand and master the techniques of oral hygiene practices. This study aimed to analyze the influence of Braille Dental Education (DBE) against Oral Hygiene in blind children.Pre-experimental research design with the group pre-posttest design, further examination Plaque Index before the intervention. Intervention is given on a sample in the form of DBE and then evaluated at day 21. The outputs or outcomes in this study of assessment of the degree oral hygiene using the Plaque Index and DBE-shaped booklet. The research sample using purposive sampling method. Data analysis using descriptive statistics in the form of tables (boxplot or diagram), then the bivariate analysis using the non-parametric Wilcoxon to determine changes in oral hygiene on the results of the pretest to posttest results. Analysis of the data in this study using a computer program to test the hypothesis based on a significance level of 0.05 with 95% confidence level.The results of the analysis of the difference in oral hygiene change from pretest to posttest showed no significant changes, indicated by Z = -3.126 and p = 0.002 (p 0.005). It can be concluded that the hypothesis that there was an effect on oral hygiene DBE in blind children is acceptable because it is essentially a state intelligence of blind children is not different from normal children, and therefore requires an approach and good communication in handling it. Key words : Dental Braille Education (DBE), Oral Hygiene, Children with Visual Impairment